Mapping the uncertainties in internet-based clinical trials: a systematic review and qualitative study - Brice, A (2017)
This thesis maps the growth of the use of internet technologies in randomised controlled trials in health care and public health, and explores the methodological and ethical issues that arise from their use from the perspective of researchers and participants. Online clinical trials are growing in number, and claim to offer benefits for researchers and participants, providing solutions to some of the inherent problems associated with traditional trials. However, little is known about how many internet-based trials have been conducted, what methodological research has been undertaken, or what impact the new technologies might have on researcher or participant experience. The thesis followed a step-by-step approach, using information science, research synthesis, and qualitative methods. The creation of a database of internet-based clinical trials established that they have grown rapidly in number, use internet technologies primarily to deliver an intervention, predominantly in behavioural, mental health, or life-style public health settings. A two-stage systematic review, comprising a descriptive map and a qualitative synthesis, established what is known about the methods, conduct or participant experience in internet-based trials. A qualitative primary study was then carried out, based on the findings of the review, to further explore the views, attitudes and experiences of researchers, participants and the public, into the motivations, benefits or barriers to taking part in internet-based clinical trials. Themes emerging from the research suggest complex interactions between design and technology, particularly in the area of participant characteristics and choice; convenience versus intrusion; impact of time and place; the pace of change and impact of societal changes in the use of technology. A range of ethical considerations emerged, including the nature of informed consent, ethical approval, and the need for a systematic approach to patient and public involvement. Recommendations are made to help inform and improve research practice in the digital age.